Designing a Model for Sustainable Cultural Development of Iranian Public Sports - Behzad Ahadi, Mir Hasan SeyedAmeri, Mohammad Rasoul Khodadadi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the study was to design a model for sustainable cultural development of Iranian public sports. The study was applied in terms of purpose and descriptive (quantitative and qualitative) in terms of method. It was conducted using a survey method based on structural equation modeling (SEM). The population of study was all the employees of the sports and youth departments and Provincial Municipal Sports Organization. The sample size was determined as 384 people selected among five provinces according to Cochran's formula using stratified-cluster sampling method. The components of sustainable cultural development of Iranian public sports were determined using library studies and consensus of the experts in five scales and 58 subscales (qualitative method) and the intended model was designed using the samples' opinions (quantitative method). The results of confirmatory factor analysis (CFA) indicated the good fit of sustainable cultural development model of Iranian public sports in five scales: “attitude,” “participation and solidarity,” “management and workforce” “technology, media and advertisement” and “optimization.”